2023
DOI: 10.3390/pharmaceutics15071891
|View full text |Cite
|
Sign up to set email alerts
|

Montelukast and Telmisartan as Inhibitors of SARS-CoV-2 Omicron Variant

Abstract: Earlier studies with montelukast (M) and telmisartan (T) have revealed their potential antiviral properties against SARS-CoV-2 wild-type (WT) but have not assessed their efficacy against emerging Variants of Concern (VOCs) such as Omicron. Our research fills this gap by investigating these drugs’ impact on VOCs, a topic that current scientific literature has largely overlooked. We employed computational methodologies, including molecular mechanics and machine learning tools, to identify drugs that could potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…We have screened the anti-AD and anti-diabetic drugs (either already marketed or in clinical trials) against their ability to bind to and inhibit the LPAR receptor activity, the SPIKE protein, and interfere with LPAR-SPIKE protein interaction. Identifying SPIKE protein inhibitors is important, as they directly target a key component of the virus's entry and replication process 84 . Throughout the screening, it was observed that the anti-AD drugs, including Lupron, Nilotinib, Telmisartan, CORT108297, neflamapimod, and bromocriptine, displayed a better binding affinity with the LPARs, the SPIKE, and hinder LPARs-SPIKE protein complex than the standard compounds.…”
Section: Discussionmentioning
confidence: 99%
“…We have screened the anti-AD and anti-diabetic drugs (either already marketed or in clinical trials) against their ability to bind to and inhibit the LPAR receptor activity, the SPIKE protein, and interfere with LPAR-SPIKE protein interaction. Identifying SPIKE protein inhibitors is important, as they directly target a key component of the virus's entry and replication process 84 . Throughout the screening, it was observed that the anti-AD drugs, including Lupron, Nilotinib, Telmisartan, CORT108297, neflamapimod, and bromocriptine, displayed a better binding affinity with the LPARs, the SPIKE, and hinder LPARs-SPIKE protein complex than the standard compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The Bio-Layer Interferometry experiment results indicate a K D of 3.892 mM for the interaction between the S protein and montelukast. However, different articles present diverse perspectives on the binding site. ,, Due to the lack of crystal structure data for the S protein and montelukast, the binding site cannot be conclusively determined. Clinical studies report that elderly asthmatic patients receiving montelukast demonstrated a significant reduction in SARS-CoV-2 infections compared to those not treated with montelukast .…”
Section: Dual-target Inhibitors Of Sars-cov-2mentioning
confidence: 99%